Aqueous Plant Extracts as Eco-Friendly Biostimulants Enhancing Germination and Early Growth of Durum Wheat under Salinity Stress - Brahim, Imene; Zaaboubi, Siham; Djerah, Abdelghani; Ben Khemiss, Akram (Annals of Arid Zone, 2025)
Salinity is a major factor limiting wheat production in arid and semi-arid regions. This study evaluated the effects of aqueous extracts from Artemisia herba-alba (white sagebrush) and Rosmarinus officinalis (rosemary) on the germination of durum wheat (Triticum durum, cv. Simeto) under saline conditions. Seeds were treated with different extract concentrations and exposed to varying levels of NaCl. Germination parameters, including total germination percentage, corrected germination, daily germination, germination index, germination speed coefficient, and final germination percentage, were recorded over six days. Results showed that rosemary extracts, especially at low doses, significantly improved germination rate and seed vigor, probably due to the antioxidant properties of phenolic compounds present in extract. In contrast, high concentrations of rosemary extracts reduced germination, indicating potential phytotoxicity. Statistical analysis confirmed that both extract type and concentration, as well as salt stress, significantly affected germination traits. These findings suggest that controlled application of rosemary extracts can be an effective, natural, and low-cost strategy to mitigate the negative effects of salinity on durum wheat germination. This approach could contribute to enhancing wheat production in saline-prone areas while minimizing reliance on chemical treatments.